Pembentukan Spiritualitas Kristen Melalui Latihan Rohani Personal dalam Konteks Saat Ini - Otto, Ottovianus; Sukamto (JURNAL LUXNOS, 2023)
Abstract: In the current development of the modern world, spirituality is experiencing a decline, because quite a few think that spirituality is an unimportant thing that must be possessed as humans created by God who are in the image and likeness of God. The author describes the formation of spirituality through spiritual practice. Spiritual practice gives people an understanding of how to realize God’s unlimited love for themselves in Jesus Christ who atoned for human sins through His death and resurrection from the dead. Spiritual practice is training one’s mind, spirit and emotions, so that one becomes closer to God, for example personal prayer, Bible study, fasting, Sunday worship, community cell seminars and service as part of the process of forming spirituality. The research method used for this writing is a qualitative method by observing experiences and reviewing literature. The analysis used is descriptive in nature with a study of practical theology. Through spiritual practice, believers will experience the formation of spirituality. Spirituality is a power that a person has to be able to have strength, goodness, holiness, obedience and sensitivity in Jesus Christ. Abstrak: Dalam perkembangan dunia modern saat ini, spiritualitas mengalami kemerosotan. Sebab tidak sedikit menganggap bahwa spiritualitas adalah hal tidak penting yang harus dimiliki sebagai manusia ciptaan Tuhan yang segambar dan serupa dengan Allah. Penulis mendeskripsikan pembentukan spiritualitas melalui latihan rohani. Latihan rohani memberikan pemahaman kepada setiap orang bahwa untuk mewujudkan kasih Allah yang tidak terbatas bagi dirinya sendiri dalam Yesus Kristus yang telah menebus dosa manusia melalui kamatiandi dan kebangkitan-Nya dari antara orang mati. Latihan rohani adalah melatih sebuah pikiran, roh dan emosi, sehingga menjadi lebih dekat dengan Tuhan, misalnya doa pribadi, studi Alkitab, puasa, ibadah minggu, komunitas sel, seminar dan pelayanan sebagai bagian dari proses pembentukan spiritualitas. Metode penelitian yang digunakan untuk penulisan ini ialah metode kualitatif dengan cara pengamatan, pengalaman, dan tinjauan pustaka. Analisa yang digunakan bersifat deskrisi dengan kajian teologi praktik. Melalui latihan rohani orang percaya akan mengalami pembentukan pembentukan spiritualitas. Spiritualitas adalah sebuah kekuatan yang dimiliki seseorang untuk bisa memiliki kekuatan, kebaikan, kesucian, ketaatan dan kepekaan di dalam Yesus Kristus.